EVALUASI MANAJEMEN PASAR TRADISIONAL BERDASARKAN ASPEK PELAYANAN PRIMA (STUDI KASUS PASAR TRADISIONAL PETERONGAN SEMARANG) - Vinda Adeliana; Mohammad Agung Ridlo; Agus Rochani (Universitas Islam Sultan Agung Semarang, 2017)
Efforts to control the management of traditional markets in terms of service excellence is expected to be carried out in synergy and more directed to the traders, buyers and market manager Peterongan. In His understanding of management's evaluation of traditional markets in terms of excellent service performed quantitative descriptive approach (quantitative approach) with a rationalistic approach. Through this approach, the researchers were able to find common ground as well as perceptions of a diverse range of different data. As a measure of evaluation used 6 main parameters, which include a) the effectiveness, b) efficiency, c) adequacy, d) equity, e) responsiveness, f) accuracy. From the analysis conducted by researchers concluded that management is not optimal Peterongan market so that the evaluation results in terms of excellent service said to be